Integration development trend of the internet of vehicles industry - Libo TANG; Chen KANG (Dianxin kexue)
Starting from communication technology evolution,the ability of communication technology to support automatic driving was studied.The upgrade trend of internet of vehicles services and the domestic and international policies were proposed.A major breakthrough in China’s internet of vehicles policy and industry was analyzed,with a good development environment.The integration and accelerated development trend of the internet of vehicles industry was concluded.